Dialectics of religious discourse, radicalism and terrorism - Ni Made Sumaryani (Life and Death: Journal of Eschatology, 2024)
An in-depth study conducted in the context of globalisation and modern social dynamics focuses on religious discourse, radicalism and terrorism. The complex interactions between religious rhetoric, radical understandings, and the emergence of acts of terrorism are discussed in this article. This research explores how religious discussions can be a fertile ground for the emergence of radical ideologies, which eventually lead to acts of terrorism, by integrating theological, psychological, and social perspectives. The research aims to gain a better understanding of the components that influence the radicalisation process by identifying the ways in which religious discourse supports radicalism. The data in this study was obtained through observation and literature review, and analysed by content analysis. This study shows that understanding how religion, radicalism and terrorism interact is crucial to stopping and countering threats to world security because radical thinking often fuels terrorism, which uses violence as a means to achieve certain goals.